Changes of serum angiogenic factors concentrations in patients with diabetes and unstable angina pectoris - Gui, Chun (BioMed Central, 2013)
BACKGROUD: Diabetic microvascular changes are considered to be influenced by angiogenic factors. As a compensatory mechanism, the expression of some angiogenic factors are elevated in ischemic myocardium. The aim of this study was to investigate the changes of serum angiogenic factors, and the association among these angiogenic factors, the severity of coronary artery stenosis and collateral vessels form in patients with diabetes and unstable angina pectoris (UAP). METHODS: 42 patients with diabetes (diabetes group), 57 patients with UAP (UAP group), and 36 age-matched healthy people (control group) were selected. Serum concentrations of angiogenic factors were measured using cytokine array technology. The severity of coronary artery stenosis was scored using the angiographic Gensini score. Coronary collateral vessels were scored according to Rentrop's classification. RESULTS: No significant differences in the serum concentrations of vascular endothelial growth factor (VEGF), angiopoietin-1 (Ang-1), angiopoietin-2 (Ang-2), angiogenin, angiostatin, basic fibroblast growth factor (bFGF) and platelet-derived growth factor-BB (PDGF-BB) were detected between control group and diabetes group. But in patients with diabetes complicated with UAP and in patients with UAP without diabetes, serum concentrations of VEGF and Ang-2 were elevated (p < 0.01, p < 0.01). Only serum Ang-2 concentrations were significantly correlated with Gensini score (r=0.585, p < 0.001), left ventricular end diastolic diameter (r=0.501, p < 0.001), left ventricular end systolic diameter (r=0.563, p < 0.001) and left ventricular ejection fraction (r=−0.523, p < 0.001). CONCLUSION: Serum concentrations of VEGF and Ang-2 were increased, and diabetes didn’t affect this increases in patients with UAP. Serum Ang-2 concentrations were correlated with the severity of coronary artery stenosis.